Human Rights, Realities and Possibilities - Macfarlane, L.J. author. aut Link
XI, 304 p.
Keywords: Researching the problems of human rights implementation in Western and Eastern Europe, this book uses Northern Ireland, the Republic of Ireland, Yugoslavia, and Hungary, as case studies. Other works by the author include "Violence and the State", and "Political Disobedience".